The effects of external and internal focus of attention on physiological responses during running - Ziv, G.; Meckel, Y.; Lidor, R.; Rotstein, A. (Journal of Human Sport & Exercise, 2012)
The purpose of this study was to examine the influence of external focus of attention and internal focus of attention instructions on physiological responses in experienced adolescent basketball players (n = 17; mean age = 15.1±0.6 years). After a 10-min warm-up at a running velocity equal to 60% of the heart rate reserve, participants ran on a treadmill under two 10-min conditions: (a) internal focus instructions - focusing on the legs and running motion, and (b) external focus instructions - focusing on a film of a basketball game that did not provide visual feedback on running speed. It was found that oxygen consumption and respiratory exchange ratio did not significantly differ among the three conditions. It was concluded that an external focus of attention that does not provide additional visual feedback pertinent to the task of running (e.g., a film clip from the runner's perspective that shows advancing in a virtual environment) does not affect physiological measures or improve running economy.